THE INFLUENCE OF REWARD, COMPETITIVE ADVANTAGE, INNOVATION, ENTREPRENEURSHIP ON FINANCIAL PERFORMANCE IMPROVEMENT: LEARNING VARIABLES MEMODERATING COMPETITIVE ADVANTAGE AND INNOVATION ON BATIK ENTREPRENEURS IN SURAKARTA - Darmanto; Basuki Sri Rahayu; Suprihati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The goal of national development is to make Indonesian society an advanced society. Such a condition is highly desired by our nation. One way to achieve this condition is by improving the performance of batik entrepreneurs in Surakarta. The purpose of this study is to formulate the positive and significant influence of rewards on financial performance, the positive and significant influence of competitive advantage on financial performance. The positive and significant influence of innovation on financial performance. The positive and significant influence of entrepreneurship on financial performance. Learning variables moderate competitive advantage and innovation on financial performance. This study was conducted on Batik entrepreneurs in Surakarta, namely in the Laweyan Batik village and the Kauman Batik village as well as in the Klewer market and the Pusar Grosir Solo shopping center. A sample of 100 was selected using the convenience sampling technique, the analysis used was (SEM) Structural Equation Model. This is used to test the influence of Independent variables consisting of reward variables, competitive advantage, innovation, entrepreneurship on financial performance, The role of learning variables in moderating competitive advantage and innovation on the financial performance of batik entrepreneurs in Surakarta. The results of this study are all hypotheses formulated are proven. 1. Proving the existence of a positive and significant influence of rewards on financial performance 2. Positive and significant influence of competitive advantage on financial performance. 3. Positive and significant influence of innovation on financial performance. 4. Positive and significant influence of entrepreneurship on financial performance. 5. Positive significant influence of learning on financial performance. 6. Learning variables moderate competitive advantage and innovation on financial performance. Keywords: 1. Reward 2, competitive advantage_3, innovation 4. Entrepreneurship_5, Learning